SISTEM INFORMASI REKOMENDASI KLINIK KESEHATAN MENGGUNAKAN ALGORITMA SLOPE ONE DAN TERM FREQUENCY RANKING - Leka Destrilia; Alam Rahmatulloh; Neng Ika Kurniati (Teknik Informatika, 2019)
Public attention to the place of health clinics greatly affect the needs that are very important in their lives, there are health clinics scattered in the Tasikmalaya area. The community does not only think about clinics that are worth visiting but also thinks about the actions given to patients suffering from certain diseases to be handled by medical workers, and also viewed from the facilities provided to provide comfort for the community. Therefore an application is needed to provide health clinic recommendations. This study aims to create a health clinic recommendation system using the Slope One algorithm and Term Frequency Rank as a substitute for a manual system and provide appropriate recall. The steps to complete this research are to design, manufacture, test and improve the recommendation system. The results of the study were in the form of a website-based health clinic recommendation system application. From the tests that have been done, it can be seen that the design of a health clinic recommendation system can provide health clinic recommendations in accordance with the Slope One algorithm and Term Frequency Rank algorithm designed.